Free fatty acid binding pocket in the locked structure of SARS-CoV-2 spike protein - Toelzer, Christine; Gupta, Kapil; Yadav, Sathish K. N.; Borucu, Ufuk; Davidson, Andrew D.; Williamson, Maia Kavanagh; Shoemark, Deborah K.; Garzoni, Frederic; Staufer, Oskar; Milligan, Rachel; Capin, Julien; Mulholland, Adrian J.; et al. (Science, 2020)
Locking down the SARS-CoV-2 spike - Many efforts to develop therapies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are focused on the spike (S) protein trimer that binds to the host receptor. Structures of trimeric S protein show its receptor-binding domain in either an up or a down conformation. Toelzer et al. produced SARS-CoV-2 S in insect cells and determined the structure by cryo-electron microscopy. In their dataset, the closed form was predominant and was stabilized by binding linoleic acid, an essential fatty acid. A similar binding pocket appears to be present in previous highly pathogenic coronaviruses, and past studies suggested links between viral infection and fatty acid metabolism. The pocket could be exploited to develop inhibitors that trap S protein in the closed conformation. - Science, this issue p. 725 - Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), represents a global crisis. Key to SARS-CoV-2 therapeutic development is unraveling the mechanisms that drive high infectivity, broad tissue tropism, and severe pathology. Our 2.85-angstrom cryo-electron microscopy structure of SARS-CoV-2 spike (S) glycoprotein reveals that the receptor binding domains tightly bind the essential free fatty acid linoleic acid (LA) in three composite binding pockets. A similar pocket also appears to be present in the highly pathogenic severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). LA binding stabilizes a locked S conformation, resulting in reduced angiotensin-converting enzyme 2 (ACE2) interaction in vitro. In human cells, LA supplementation synergizes with the COVID-19 drug remdesivir, suppressing SARS-CoV-2 replication. Our structure directly links LA and S, setting the stage for intervention strategies that target LA binding by SARS-CoV-2. - The SARS-CoV-2 spike binds linoleic acid, a key molecule in inflammation, immune modulation, and membrane fluidity. - The SARS-CoV-2 spike binds linoleic acid, a key molecule in inflammation, immune modulation, and membrane fluidity.
Gesehen am 04.02.2021